The doubled life of Dietrich Bonhoeffer : women, sexuality, and Nazi Germany - Reynolds, Diane (Diane S.) (James Clarke & Co, 2017)
A study of the great German theologian Dietrich Bonhoeffer analysing the role of the women in his life and his struggles with his sexuality.